High Prevalence of Rodent-Borne Bartonella spp. in Urbanizing Environments in Sarawak, Malaysian Borneo - Blasdell, Kim R.; Perera, David; Firth, Cadhla (The American Society of Tropical Medicine and Hygiene, 2018)
Rodents are the most prominent animal host of Bartonella spp., which are associated with an increasing number of human diseases worldwide. Many rodent species thrive in urban environments and live in close contact with people, which can lead to an increased human risk of infection from rodent-borne pathogens. In this study, we explored the prevalence and distribution of Bartonella spp. in rodents in urban, developing, and rural environments surrounding a growing city in Sarawak, Malaysian Borneo. We found that although Bartonella spp. infection was pervasive in most rodent species sampled, prevalence was highest in urban areas and infection was most commonly detected in the predominant indigenous rodent species sampled (Sundamys muelleri). Within the urban environment, parks and remnant green patches were significantly associated with the presence of both S. muelleri and Bartonella spp., indicating higher localized risk of infection for people using these environments for farming, foraging, or recreation.